The effectiveness of teaching methods for preparing teacher education students to teach road safety-related content - von Beesten, Silke; Bresges, André (Frontiers in Education, 2025)
IntroductionRoad traffic accidents account for numerous fatalities worldwide, disproportionately affecting vulnerable groups such as children. To counteract this trend, innovative educational approaches are essential, integrating road safety into school curricula. This study presents a novel teaching model for student teachers specializing in traffic physics. The model employs a holistic and interdisciplinary approach to foster safety awareness during teacher training and to prevent accidents effectively.MethodsThe teaching approach combines theoretical concepts of traffic physics with real-world applications. Schools serve as testing grounds where prospective teachers conduct traffic analyses, identify hazardous zones, and examine physical laws such as traffic density and speed patterns, alongside psychological aspects like behavioral deviations. Qualitative methods, including design thinking and interviews with road users, promote empathy and provide deeper insights into the challenges of road safety. Prototypes, such as optimized traffic signs and technology-driven safety solutions, illustrate practical applications and solutions.ResultsThe active involvement of students in analyzing and resolving traffic issues enhanced their understanding of physical principles. The combination of theory and practice improved hazard perception, risk assessment, and empathy toward road users. The developed prototypes translated learning objectives into actionable safety measures and demonstrated potential for scalable applications. An evaluation tool ensured the objective assessment of learning outcomes, incorporating pedagogical principles and subject-specific standards.DiscussionThe findings emphasize the importance of integrating traffic physics into school education. This context-oriented approach connects learning with students' everyday experiences, fostering cognitive, emotional, and behavioral dimensions of road safety. By involving prospective teachers, the program not only enhances their individual competencies but also contributes to a broader societal impact, improving road safety education. This study outlines an innovative framework for teaching traffic physics that integrates theoretical knowledge with practical application to promote road safety. The model provides a replicable and scalable solution for embedding safety education into school curricula, addressing a critical public health issue effectively.